Peran Guru Pendidikan Agama Islam dalam Membentuk Akhlakul Karimah Peserta Didik - Najamudin Najamudin; Dwi Muliati (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
This study aims to analyze the fundamental role of Islamic Religious Education (PAI) teachers in shaping the noble character of students using a qualitative approach through literature review techniques. Data were collected from various scientific sources published between 2020 and 2026 and analyzed using content analysis methods, which included stages of reduction, categorization, and conceptual synthesis. The main focus of this study is to examine how PAI teachers integrate the values of tawhid and worship into the daily behavior of students, so that religious education does not merely remain at the cognitive level but manifests in noble character. The findings indicate that PAI teachers play a strategic role as murabbi, mu’allim, and muaddib, whose success is determined by the integration of pedagogical, professional, social, personality, and spiritual competencies. Amid the dynamic challenges of the digital era, teachers are required to revitalize their roles not only as educators but also as moral exemplars (uswatun hasanah) and agents of character transformation. The synergy between teachers' competencies and consistent exemplification is the key to safeguarding the students' morality and fostering a resilient personality in the school environment.